Twenty years′ follow-up of a de-epithelialised turnover flap - Gopalakrishna A; Pavan Kumar T (Indian Journal of Plastic Surgery)
The authors have used the de-epithelialised turnover flap (Thatte′s Flap) for covering compound defects over the tendo-achilles in 31 patients in the period covering 1980-2000. Two of these patients have come up for follow-up after 20 years. In this late follow-up, the results are good and the tendon which was bridged by the dermis of the flap is functioning to allow the patients to stand on their toes. The de-epithelialised turnover flap is a simple and easy technique giving good long-term results. In spite of all the new advances in flap coverage, the de-epithelialised turnover flap is a good alternative for the tendo-achilles area in the armamentarium of a plastic surgeon.